Community Math Stations as a Learning Opportunity for Preservice Teachers. Issue 10 (26th November 2021) - Verzosa, Debbie Marie B.
Abstract : This paper describes a project that sought to simultaneously facilitate the mathematical learning of both preservice teachers (PSTs) and schoolchildren. The project involved the organization of community Math Stations related to research-based number sense activities and was integrated within two university-level courses. This article describes strategies for addressing the challenges associated with organizing such a project and shows how the project contributed to the learning of PSTs with respect to content knowledge, pedagogical content knowledge, and general pedagogy. Suggestions for organizing a similar project in other settings are also discussed.